GENDER DIFFERENCES IN READING STRATEGIES AMONG VOCATIONAL HIGH SCHOOL STUDENTS (RETAIN, 2020)
Second language learners use different reading strategies so they can comprehend a text. Nevertheless, generally recognizing the value of reading strategies is that some work on whether or not ESL male and female have similar or different strategic reading habits has different results. This research was conducted to determine what reading strategies are reported to be used by male and female students when they are taught using three-phase approach and whether the use of such reading strategies varies between male and female or not. Researcher performed this study in quantitative approach in survey design. The system is questionnaire. The researcher was conducted as the subject in SMKN 1 JOMBANG, with 10th grade students. The result of the study showed that both male and female student actively applied some reading strategies in their reading process. Male and female have similarity in their preferences in using reading strategy, they also have differences in using some reading strategy.